Novel Biodegradable Polymeric Microparticles Facilitate Scarless Wound Healing by Promoting Re-epithelialization and Inhibiting Fibrosis - Nosenko, Maxim A.; Moysenovich, Anastasia M.; Zvartsev, Ruslan V.; Arkhipova, Anastasia Y.; Zhdanova, Anastasia S.; Agapov, Igor I.; Vasilieva, Tamara V.; Bogush, Vladimir G.; Debabov, Vladimir G.; Nedospasov, Sergei A.; Moisenovich, Mikhail M.; Drutskaya, Marina S. (Frontiers in Immunology, 2018)
Despite decades of research the goal of achieving scarless wound healing remains elusive. One of the approaches, treatment with polymeric microcarriers, was shown to promote tissue regeneration in various in vitro models of wound healing. The in vivo effects of such an approach are attributed to transferred cells with polymeric microparticles functioning merely as inert scaffolds. We aimed to establish a bioactive biopolymer carrier that would promote would healing and inhibit scar formation in the murine model of deep skin wounds. Here we characterize two candidate types of microparticles based on fibroin/gelatin or spidroin and show that both types increase re-epithelialization rate and inhibit scar formation during skin wound healing. Interestingly, the effects of these microparticles on inflammatory gene expression and cytokine production by macrophages, fibroblasts, keratinocytes are distinct. While both types of microparticles as well as their soluble derivatives, fibroin and spidroin, significantly reduced the expression of profibrotic factors Fgf2 and Ctgf in mouse embryonic fibroblasts. However, only fibroin/gelatin microparticles induced transient inflammatory gene expression and cytokine production leading to an influx of inflammatory Ly6C+ myeloid cells to the injection site. The ability of microparticle carriers of equal proregenerative potential to induce inflammatory response may allow their subsequent adaptation to treatment of wounds with different bioburden and fibrotic content.